#NeverLeaveTheDogBehind: How climbers' dogs perform mountain landscapes. (17th February 2019) - Mort, Helen
Abstract : This article considers the performance of climbers' identities in mountain landscapes through the images they take of their dogs in wild places. Drawing on the notion of a dramaturgy of self-presentation (Goffman, 1959 ), it seeks to apply this theory to an age in which social media platforms - particularly Instagram - have changed the way we present ourselves and how we connect with mountain landscapes. It draws upon semi-structured written interviews with a range of outdoor enthusiasts and blends this with personal experience, seeking to address questions like: are pictures of dogs in the mountains inherently more appealing than pictures of people? Why do we want to photograph our dogs in the hills? What do we think these images say about us?